EVALUATION OF THE ACCURACY LEVEL OF STABBING OF BANDA ACEH CITY FENCING ATHLETES - irwandi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aimed to evaluate the level of jab accuracy of fencers in Banda Aceh. Eight fencers in Banda Aceh were included in the study and asked to perform 20 jabs in a controlled trial. The jab accuracy was calculated based on the number of jabs that successfully hit the target. The results showed significant variation in the jab accuracy of the athletes. Two athletes (25%) managed to achieve an accuracy level between 80% and 100% and were categorized as Very Good. Two other athletes (25%) were in the Good category with an accuracy of 70%-79%, while two other athletes (25%) were in the Fair category (60%-69%). In addition, one athlete (12.5%) had a jab accuracy between 50% and 59% and was included in the Poor category, while one other athlete (12.5%) was in the Very Poor category with an accuracy of 40%-49%. The overall average jab accuracy was 70.63% with a standard deviation of 14.61%, indicating variation in the athletes' performance. Based on these results, it is recommended to provide more intensive training and focus on improving the technique, concentration, and physical condition of athletes to achieve more optimal performance in the future.